THE HISTORIC BACKGROUND OF â€œLLAIKO VIMAâ€ NEWSPAPER (1945-2012) - Polo, Olieta (European Scientific Journal, ESJ, 2014)
The aim of this paper is to give a general view of the history of â€œLlaiko Vimaâ€ newspaper of the Ethnic Greek Minority in Albania from the year 1945-2012 in which will be mentioned the general characteristics of â€œLlaiko Vimaâ€ newspaper and mainly its purpose, its publishing team, its circulation, its personality and its ideology, the ideological action frame of its correspodents, its economics and circulation.